Combined ingestion of protein and free leucine with carbohydrate increases postexercise muscle protein synthesis in vivo in male subjects - Koopman, René; Wagenmakers, Anton J M; Manders, Ralph J F; Zorenc, Antoine H G; Senden, Joan M G; Gorselink, Marchel; Keizer, Hans A; van Loon, Luc J C (American journal of physiology: endocrinology and metabolism, 2005)
The present study was designed to determine postexercise muscle protein synthesis and whole body protein balance following the combined ingestion of carbohydrate with or without protein and/or free leucine. Eight male subjects were randomly assigned to three trials in which they consumed drinks containing either carbohydrate (CHO), carbohydrate and protein (CHO+PRO), or carbohydrate, protein, and free leucine (CHO+PRO+Leu) following 45 min of resistance exercise. A primed, continuous infusion of L-[ring-13C6]phenylalanine was applied, with blood samples and muscle biopsies collected to assess fractional synthetic rate (FSR) in the vastus lateralis muscle as well as whole body protein turnover during 6 h of postexercise recovery. Plasma insulin response was higher in the CHO+PRO+Leu compared with the CHO and CHO+PRO trials (+240 +/- 19% and +77 +/- 11%, respectively, P < 0.05). Whole body protein breakdown rates were lower, and whole body protein synthesis rates were higher, in the CHO+PRO and CHO+PRO+Leu trials compared with the CHO trial (P < 0.05). Addition of leucine in the CHO+PRO+Leu trial resulted in a lower protein oxidation rate compared with the CHO+PRO trial. Protein balance was negative during recovery in the CHO trial but positive in the CHO+PRO and CHO+PRO+Leu trials. In the CHO+PRO+Leu trial, whole body net protein balance was significantly greater compared with values observed in the CHO+PRO and CHO trials (P < 0.05). Mixed muscle FSR, measured over a 6-h period of postexercise recovery, was significantly greater in the CHO+PRO+Leu trial compared with the CHO trial (0.095 +/- 0.006 vs. 0.061 +/- 0.008%/h, respectively, P < 0.05), with intermediate values observed in the CHO+PRO trial (0.0820 +/- 0.0104%/h). We conclude that coingestion of protein and leucine stimulates muscle protein synthesis and optimizes whole body protein balance compared with the intake of carbohydrate only.